Sustainable development, climate change, and renewable energy in rural Central America - Ley, D (2013)
Can rural renewable energy projects simultaneously meet the multiple goals of sustainable development, climate change mitigation and climate change adaptation? If so, under what conditions? Rural communities throughout Latin America have increasingly suffered the impacts of climate change and few policies exist to help them adapt to these impacts. The basic infrastructure and services that they frequently lack can be provided by low carbon technologies, potentially funded by international carbon finance flows that could enable the Millennium Development Goals of economic growth and poverty alleviation to be met while minimizing carbon emissions. This research will focus on this interrelationship among development, climate change mitigation and climate change adaptation policies and practices using political ecology to analyse community renewable energy projects in rural Central America. I assess fifteen community-owned renewable energy projects in Guatemala and Nicaragua to analyse whether current renewable energy projects are achieving these goals in an integrated way. The projects were established primarily as development, emissions reductions, climate change adaptation and disaster relief. The projects are evaluated on economic, development and climate change indicators that include sustainable development, poverty alleviation, emissions reductions, and climate vulnerability. I examine how the type of common property governance, local historical and environmental background and project implementation process influence the project success in meeting multiple objectives of climate adaptation, mitigation and development. Research methods include participatory poverty assessment techniques, semi-structured interviews, stakeholder analysis, and a combination of rapid and participatory methods. The analysis of sustainable development and vulnerability used the Sustainable Livelihoods Approach methodologies and emissions reductions were calculated using standard carbon reduction methodologies. The results show that, under certain conditions, renewable energy projects can simultaneously meet these three objectives, and thus that responses to climate change can be integrated with poverty alleviation and sustainable development. Small scale hydroelectric and solar systems can reduce emissions, enable adaptation and help local livelihoods although there are numerous problems that limit the success of projects including poor design, inequitable distribution of benefits, and poorly designed governance and maintenance structures.